Adaptive Maintenance Strategy in Natural Stone Processing Industry: Integrating OEE-FMEA-Based Priority Matrix in the i-TPM-Lean+ - Ahmed Jabari; Ahmad Atif Fikri; Muhammad Alfian Mizar (Jurnal Teknik Mesin (Sinta 3), 2025)
This study proposes a hybrid model integrating total productive maintenance (TPM) and Lean Manufacturing tools to improve machine effectiveness in a marble processing company in Indonesia. High downtime, performance inefficiencies, and quality losses were identified as key contributors to low overall equipment effectiveness (OEE). A structured framework, called i-TPM-Lean+, was implemented by combining OEE measurement with failure mode and effect analysis (FMEA) to prioritize improvement strategies. TPM pillars such as Autonomous Maintenance, Planned Maintenance, and Focused Improvement were applied alongside Lean tools including 5S and single minute exchange of dies (SMED). Real operational data was collected for 30 days before and after implementation to evaluate changes in machine performance. The results revealed a substantial improvement in OEE from 59% to 70%, with notable reductions in downtime (–67%) and increases in availability (from 79% to 88%), performance (from 81% to 84%), and quality rate (from 92% to 94%). Benchmarking with other relevant studies confirmed that this integrated approach leads to enhanced machine reliability and production efficiency. The proposed model offers a practical reference for manufacturing companies seeking to improve operational performance through a combined TPM-Lean approach, supported by data-driven prioritization and systematic evaluation.